53.1k views
5 votes
F(x) = Square root of quantity x plus nine.; g(x) = 8x - 13

Find f(g(x)).
f(g(x)) = 2Square root of quantity two x minus one.
f(g(x)) = 8Square root of quantity x minus four.
f(g(x)) = 2Square root of quantity two x plus one.
f(g(x)) = 8Square root of quantity x plus nine. - 13

User Karl Reid
by
4.9k points

2 Answers

5 votes
f(x) = sqrt(x) + 9
g(x) = 8x - 13

f(g(x)) = f(8x - 3) = sqrt(8x - 13) + 9
User Torbinsky
by
5.5k points
7 votes

Answer:


2√(2x-1)

Explanation:

f(x) = Square root of quantity x plus nine.

Mathematically we can write this as:


f(x)=√(x+9)


g(x)=8x-13

We have to find
f(g(x))

So, we have to replace x in f(x) with : 8x-13.


f(g(x))=f(8x-13)

=
√(8x-13+9)

=
√(8x-4)

=
√(4(2x-1))

=
2√(2x-1)

Hence, answer is : f(g(x)) = 2 Square root of quantity two x minus one.

User Ali Shahzad
by
5.7k points